Edukasi Tentang Flour Albus pada Ibu Hamil di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2024 - Yasrida Nadeak; Ariska Fauzianty; Polma Ria Panjaita; Nova Issabella Mariance Br Napitupulu; Nail Kamila (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
In the health life of a woman there are several complaints of disease, one of the complaints that is very disturbing is fluor albus (leucorrhoea). The purpose of this outreach activity is to make young women understand the causes and treatment of vaginal discharge. This activity was carried out at the Bangun Rejo village,Deli Serdang District. This activity begins by asking questions about the knowledge of pregnant women about vaginal discharge. Followed by giving material using power point. The result of this activity is that there is an increase in pregnant women knowledge about vaginal discharge by 60%. This activity is the first step to improve reproductive health, especially for pregnant women who will one day give birth to the next generation of this nation.